1973
DOI: 10.1063/1.1662017
|View full text |Cite
|
Sign up to set email alerts
|

Predicted electron transport coefficients and operating characteristics of CO2–N2–He laser mixtures

Abstract: Calculations have been made of transport coefficients of electrons in gas mixtures for ratios CO2:N2:He of 1:1:8, 1:2:3, 1:7:30, and 1:0.25:3. New cross sections for CO2 derived from swarm experiments are used together with previously published cross sections for N2 and He. Curves are presented of the predicted electron drift velocity, transverse and longitudinal diffusion coefficients, and ionization and attachment coefficients for E/N values ranging from 10−18 to 1 × 10−15 V cm2; E is the electric field stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0
4

Year Published

1975
1975
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 371 publications
(112 citation statements)
references
References 26 publications
3
105
0
4
Order By: Relevance
“…Lowke and colleagues obtained electrical energy distribution functions for each E/N for a CO 2 /N 2 /He gas mixture [10]. Their method has been applied to a TE-CO 2 laser at greater than atmospheric pressures [11].…”
Section: Discussionmentioning
confidence: 99%
“…Lowke and colleagues obtained electrical energy distribution functions for each E/N for a CO 2 /N 2 /He gas mixture [10]. Their method has been applied to a TE-CO 2 laser at greater than atmospheric pressures [11].…”
Section: Discussionmentioning
confidence: 99%
“…But as shown in fig. 2-4, Lowke et al [38] found that the (001) cross section of Boness and Schulz [12] is about a factor of 3 too large to give consistent transport coefficients ( i.e. electron drift velocity, ionization and attachment coefficients).…”
Section: Direct Electron Impactmentioning
confidence: 99%
“…and N 2 • Thus, electron energies sufficient to excite the upper laser level occurs at lower E/N [38].…”
Section: Radial Gain Profilementioning
confidence: 99%
See 1 more Smart Citation
“…Values of D T in real gases were calculated using Boltzmann equation analyses, Monte Carlo simulations, and other numerical methods by Lowke et al (1973) for a CO 2 /N 2 /He mixture, Pitchford and Phelps (1982) and Phelps and Pitchford (1985) for N 2 , Makabe and Shimoyama (1986) and Koura (1987) for Ar or an Ar-like gas, Yachi et al (1991) and Date et al (1993) for CH 4 , etc. D T was also calculated for Ba + ions in Ar by Viehland (1994).…”
Section: Introductionmentioning
confidence: 99%